CLINICAL EFFICACY OF HIGH DOSE WATER-SOLUBLE VITAMINS SUPPLEMENTATION ON LIPID PROFILE IN PRE-HYPERTENSIVE SUBJECTS - TALIKOTI, PRASHANTH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Background: Hypertension (HTN) is one of the preventable cardiovascular diseases (CVD) but it causes significant morbidity and mortality. Recently, incidence of pre-hypertension is increasing and it has a greater chance of developing into HTN. Dyslipidemia is one of the main risk factors for the development of CVD among the pre-hypertensive subjects. Water soluble vitamins display potent antioxidant and anti-inflammatory effects and also elicits favorable effect on lipid profile in HTN. In this backdrop, the present study was carried out to evaluate the supplementation of water-soluble vitamins on lipid profile in pre-hypertensive patients. Methods: This was a randomized, single blinded, and placebo-controlled study conducted on 60 pre-hypertensive subjects and was allocated into water soluble vitamins group (n=30) and received Becosules capsule for 4 months and placebo group (n=30) received starch capsule for 4 months. The blood was withdrawn at 2–4 months and the lipid profiles such as total cholesterol, triacylglycerol, HDL cholesterol (HDL-C), low-density lipoprotein (LDL)-C, and VLDL were measured. Then, the lipid profiles were compared with in the group and between the groups at 2–4 months using two-way repeated measures ANOVA. Results: In this study, the triglycerides and VLDL level were significantly (p<0.05) decreased in water soluble vitamin groups as compared to the placebo groups. Meanwhile there was no significant alteration in the total cholesterol, HDL-C, and LDL-C level between the groups. Conclusion: Thus, the study shows that water soluble vitamins displayed significant anti-dyslipidemia effect in pre-hypertension and might also confer protection in the future progression of HTN.